Does Age Influence How Patients Rate Their Experience of Care after Total Knee Arthroplasty? - Gwam, Chukwuweike U.; Mistry, Jaydev B.; Mohamed, Nequesha; Chughtai, Morad; Thomas, Melbin; Mont, Michael A.; Delanois, Ronald E. (The Journal of Knee Surgery, 2017)
The Centers for Medicare and Medicaid Services (CMS) have recently modified models for physician compensation with the use of patient administered surveys, such as the Press Ganey (PG). Currently, it is not well understood how the age of total knee arthroplasty (TKA) patients influences PG scores and hospital ratings. Therefore, we asked: (1) is there a difference in how patients rate PG survey elements between patients < 50 years of age, 50 to 80 years of age, and > 80 years of age and (2) what factors influence PG overall hospital rating in the various age groups? The PG database from our institution was queried from November 2009 to January 2015, yielding 728 patients who received a primary TKA. Patients were stratified by age at the time of surgery, based on those < 50 years (n = 43), 50 to 80 years (n = 639), and > 80 years of age (n = 46). The means for each domain was calculated and multiple regression analyses were performed separately for the three cohorts, to assess the influence (β-weight) of each domain on overall hospital ratings. Chi-square tests and Student's t-tests were performed appropriately to assess differences in categorical and continuous data between the three cohorts. No significant difference in mean scores was observed in any individual domain category between the three age groups. Communication with nurses had a significant influence on overall hospital rating in all three age groups. In addition, perception of pain demonstrated a significant influence on overall hospital rating for patients < 50 years of age (β = 0.807, p = 0.011) and those 50 to 80 years of age (β = 0.248, p = 0.014). For patients who were < 50 years of age, communication regarding medication had a significantly negative influence on overall hospital ratings (β = − 0.387, p = 0.025). For patients who were > 80 years of age, staff responsiveness (β = 0.403, p = 0.002) also significantly influenced overall hospital ratings. With physician reimbursement partially dependent on patient-reported experiences of care, orthopaedists must recognize and improve on the factors that affect patient satisfaction to avoid financial penalties. Although age was found to not have a global effect on PG scores after TKA, the factors that patients consider most important during their experience of care may vary by age group.
Keywords: total knee arthroplasty; Press Ganey; age; reimbursement; survey elements